REKONSTRUKSI KEDUDUKAN KETETAPAN MPR DALAM SISTEM KETATANEGARAAN INDONESIA - Widayati, Widayati; Absori, Absori; Fitriciada Azhari, Aidul (Jurnal Media Hukum, 2014)
Amendments of UUD 1945 Constitution to change the state system of Indonesia, including changes in state institutions, especially institutions MPR. After amendment of 1945 Constitution, MPR position parallel with other state institutions, and the authority of MPR also changed. MPR no longer as the highest state institutions and actors sovereignty of the people so that their authority is very limited. MPR no longer authorized to elect the President and Vice President, and is no longer authorized to establish GBHN. By not competent MPR sets GBHN, then MPR is not authorized to establish to form TAP MPR. It becomes polemic when Law No. 12/2011 2011 places TAP MPR to the kind and hierarchy of Laws and Regulations. Therefore, This research will analize the development of position of TAP MPR related to authority of MPR, then reconstructed to the position of TAP MPR on Indonesiaâs constitutional system. The method used to analyze is normative. In the reconstruction of the position of TAP MPR carried by the fifth amendment of the 1945 Constitution to strengthen the MPR institutions and give the highest authority MPR, one of which is to develop a state policy that is poured into legal products MPR.